The effect of training two selected karate-hand techniques on hand stereotypic movements in autistic boy (Case study) - Fatimah Bahrami; Ahmadreza Movahedi; Seyed Mohammad Marandi; Shila Safavi; Zahra Molakarimi (Vesnu Publications, 2013)
Introduction: Stereotypy is one of the main features of children with autism. These behaviors are associated with deficit in learning processes, social skills acquisition, increased family stress, and self-injuries behaviors. The purpose of the present study was aimed to investigate the effectiveness of two selected Karate-hand techniques on hand stereotypic movements in a boy with autism. Materials and Methods: The participant was a 10 years old boy with autism. He asked to take part in some exercise sessions. The exercise phase was preceded and followed by some baseline phases. In baseline phases, the participant did not receive any exercise. Change in the frequency of stereotypic hand movements was assessed by observations during 15 minute periods immediately before and after exercise while participant engaged in routine classroom activities. Observations also occurred in the same time periods on no-exercise days during all phases. Results: Results showed that training two karate hand techniques led to reduction of 44.12 percent in stereotypic hand movements in subject. Conclusion: The present study showed that training two karate hand techniques might reduce the stereotypic hand movements in a child with autism. Since the result has came out from a single case study, it could be suggested that more experimental studies can be carried out on autistic participants to investigate whether this technique effect on hand movements. Keywords: Zuki, Gedan barai, Karate, Autism, Stereotypic movement